Bonding layer with strong pinning effect as well as preparation method and application of bonding layer
By processing scratches on the surface of the bonding layer of the thermal barrier coating and pre-oxidation and oxidation treatment, a strong pining bonding layer is formed, which solves the problem of peeling of the thermal barrier coating and significantly improves the anti-oxidation and peeling properties. .
Patent Information
- Application Number
- CN202411567725.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing thermal barrier coating is prone to peel off at the ceramic surface-oxide-bonding layer interface, resulting in the failure of the thermal barrier coating.
The preparation method of the strong pining effect bonding layer is adopted, including preparing the bonding layer coating on the substrate surface, surface processing obtains interval-distributed scratches, and through pre-oxidation and oxidation treatment, forming an oxide uniformly distributed in a dot matrix. Provides higher bonding power to the bonding layer.
It greatly improves the antioxidant performance of the bonding coating and the anti-flaking performance of the oxide layer, and extends the service life of the thermal barrier coating.
Smart Images

Figure CN119433530A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material technology, and in particular to a strong pinning effect bonding layer and a preparation method and application thereof. Background Art
[0002] Thermal barrier coatings (TBCs) are a layer of ceramic coatings that are deposited on the surface of high-temperature resistant metals or superalloys. The TBCs act as a heat insulator for the substrate material, lowering the substrate temperature so that devices made of them (such as engine turbine blades) can operate at high temperatures and can increase the thermal efficiency of devices (engines, etc.) by more than 60%.
[0003] Thermal barrier coatings are mainly composed of a ceramic surface layer and a bonding layer. An oxide layer is formed on the bonding layer surface between the ceramic surface layer and the bonding layer. The bonding layer is used to connect the base material and the ceramic surface layer in the thermal barrier coating system, playing a connecting role. The oxide layer provides antioxidant properties for the thermal barrier coating. Failure of thermal barrier coatings usually occurs at the interface of the ceramic surface layer-oxide layer-bonding layer. The initiation and expansion of interface cracks causes the thermal barrier coating to peel off. Summary of the invention
[0004] The purpose of the present application is to provide a strong pinning effect bonding layer and a preparation method and application thereof, aiming to solve the problem of peeling of existing thermal barrier coatings.
[0005] To achieve the above objectives, the present application provides a method for preparing a strong pinning effect bonding layer, comprising:
[0006] preparing a bonding layer coating on a substrate surface;
[0007] Processing the surface of the bonding layer coating to obtain scratches distributed at intervals;
[0008] The adhesive layer coating with the scratches is pre-oxidized and oxidized in sequence to obtain the adhesive layer with strong pinning effect.
[0009] In some embodiments, preparing a bonding layer coating on the surface of a substrate includes: preparing the bonding layer coating on the surface of the substrate by laser cladding technology.
[0010] In some embodiments, the laser power of the laser cladding is 1200W to 1800W, and the laser speed is 20mm / s to 100mm / s.
[0011] In some embodiments, after preparing the bonding layer coating on the surface of the substrate, the method further includes: grinding and polishing the bonding layer coating.
[0012] In some embodiments, the composition of the bonding layer coating includes, by mass percentage, Al 10-11%, Co 23-24%, Cr 19-20%, Fe 22-23%, Ni 23-24%, Y 0.5-1%, and Hf 0-0.5%.
[0013] In some embodiments, the pre-oxidation temperature is 550° C. to 850° C., and the holding time is 2 to 3 hours.
[0014] In some embodiments, the oxidation temperature is 800° C. to 1000° C., and the oxidation time is 80 to 150 hours.
[0015] In some embodiments, the interval between the scratches is 1-20 μm, and the depth of the scratches is 0.5-2 μm.
[0016] The present application also provides a strong pinning effect bonding layer, which is prepared by the above-mentioned method for preparing a strong pinning effect bonding layer.
[0017] The present application also provides the application of the strong pinning effect bonding layer prepared by the preparation method of the strong pinning effect bonding layer in the hot end component.
[0018] Compared with the prior art, the beneficial effects of this application include:
[0019] The preparation method of the bonding layer with a strong pinning effect provided in the present application obtains spaced scratches on the surface of the bonding layer coating, and sequentially undergoes pre-oxidation and oxidation treatment to form a lattice-shaped uniformly distributed oxide inside the bonding layer coating, thereby providing a strong pinning effect for the oxide layer on the surface of the bonding layer coating, providing a higher bonding force for the oxide layer, and greatly improving the antioxidant properties of the bonding layer coating and the anti-peeling properties of the oxide layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0021] Figure 1 A schematic diagram of a method for preparing a strong pinning effect bonding layer of the present application;
[0022] Figure 2 This is a schematic diagram of a strong pinning effect bonding layer prepared in this application;
[0023] Figure 3 This is a SEM image of the strong pinning effect bonding layer prepared in Example 1;
[0024] Figure 4This is a SEM image of the strong pinning effect bonding layer prepared in Example 2;
[0025] Figure 5 This is a SEM image of the strong pinning effect bonding layer prepared in Example 3;
[0026] Figure 6 This is a SEM image of the strong pinning effect bonding layer prepared in Example 4;
[0027] Figure 7 This is a SEM image of the bonding layer prepared in Comparative Example 1;
[0028] Figure 8 for Figure 7 Magnified image of the middle crack;
[0029] Fig. 9 This is a SEM image of the bonding layer prepared in Comparative Example 2;
[0030] Fig.10 This is the SEM image of the bonding layer prepared in Comparative Example 3. DETAILED DESCRIPTION
[0031] As used herein:
[0032] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0033] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0034] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0035] In these examples, parts and percentages are by mass unless otherwise indicated.
[0036] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0037] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0038] The present application provides a method for preparing a strong pinning effect bonding layer, comprising:
[0039] S100: preparing a bonding layer coating on the surface of the substrate;
[0040] S200: processing the surface of the bonding layer coating to obtain scratches distributed at intervals;
[0041] S300: pre-oxidizing and oxidizing the adhesive layer coating with the scratches in sequence to obtain the adhesive layer with strong pinning effect.
[0042] The preparation method of the bonding layer with a strong pinning effect provided in the present application obtains spaced scratches on the surface of the bonding layer coating, and sequentially undergoes pre-oxidation and oxidation treatment to form a lattice-shaped uniformly distributed oxide inside the bonding layer coating, thereby providing a strong pinning effect for the oxide layer on the surface of the bonding layer coating, providing a higher bonding force for the oxide layer, and greatly improving the antioxidant properties of the bonding layer coating and the anti-peeling properties of the oxide layer.
[0043] Among them, the substrate in step S100 can be any material that needs to be prepared with a thermal barrier coating, for example, it can be a high-temperature resistant metal or superalloy. The thermal barrier coating has a heat-insulating effect on the substrate material, reduces the substrate temperature, and enables devices made therefrom (such as engine turbine blades) to operate at high temperatures, and can improve the thermal efficiency of the device (engine, etc.) to more than 60%. The thermal barrier coating includes a bonding layer and a ceramic top layer, and the bonding layer is used to connect the substrate and the ceramic top layer.
[0044] The method for preparing the bonding layer coating on the substrate surface in step S100 may be, for example, laser cladding technology, activated combustion high-velocity fuel gas spraying technology, electric spark deposition technology, atmospheric plasma spraying technology, etc.
[0045] The bonding layer coating may be, for example, an AlCoCrFeNi-YHf oxide layer, an MCrAlY oxide layer, a PtAl oxide layer, and the like.
[0046] In some embodiments, preparing a bonding layer coating on the surface of a substrate includes: preparing the bonding layer coating on the surface of the substrate by laser cladding technology.
[0047] In some embodiments, the laser power of the laser cladding is 1200W to 1800W, for example, it can be 1200W, 1300W, 1400W, 1500W, 1600W, 1700W, 1800W or any value between 1200W and 1800W, and the laser rate is 20mm / s to 100mm / s, for example, it can be 20mm / s, 30mm / s, 40mm / s, 50mm / s, 60mm / s, 70mm / s, 80mm / s, 90mm / s, 100mm / s or any value between 20mm / s and 100mm / s.
[0048] Laser cladding is a surface protection technology that uses laser to melt alloy powder and the surface of the base material, and then forms an alloy coating on the surface of the base material after rapid solidification. The laser power and rate parameters affect the temperature, size, and cooling rate of the molten pool, and have an important impact on the microstructure and macroscopic quality of the coating. If the laser power is too high and the rate is too low, the dilution rate between the coating and the base will be too high, and the surface quality will deteriorate; if the laser power is too low and the rate is too high, it will cause problems such as coating porosity and poor performance of the overlap area.
[0049] In some embodiments, after preparing the bonding layer coating on the surface of the substrate, the method further includes: grinding and polishing the bonding layer coating to remove dirt and adhered powder on the surface of the bonding layer coating.
[0050] In some embodiments, the composition of the bonding layer coating includes, by mass percentage: Al 10-11%, Co 23-24%, Cr 19-20%, Fe 22-23%, Ni 23-24%, Y 0.5-1%, Hf 0-0.5%. AlCoCrFeNi high entropy alloy has been proven to have good oxidation resistance, and the addition of active elements such as Y and Hf can pin the oxide layer on the surface of the bonding layer coating, further improving its oxidation resistance.
[0051] In some embodiments, the pre-oxidation temperature is 550°C to 850°C, for example, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or any value between 550°C and 850°C, and the holding time is 2 to 3 hours. Pretreatment in an appropriate environment can promote the stable growth of oxide "nails" in the early stage of oxidation and improve the antioxidant performance.
[0052] In some embodiments, the oxidation temperature is 800°C to 1000°C, for example, it can be 800°C, 900°C, 1000°C or any value between 800°C and 1000°C, and the time is 80 to 150h, for example, it can be 80h, 90h, 100h, 110h, 120h, 130h, 140h, 150h or any value between 80 and 150h.
[0053] In some embodiments, the spacing distance of the scratches is 1-20μm, for example, it can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm or any value between 1-20μm, and the depth of the scratches is 0.5-2μm, for example, it can be 0.5μm, 1μm, 1.5μm, 2μm or any value between 0.5-2μm.
[0054] Micron scratches provide favorable structural conditions for the formation of oxide "nails" in the subsequent pre-oxidation process, but the scratch interval and depth directly affect the morphology and performance of the oxide "nails". If the scratch interval is too small or the scratch depth is too small, it is easy to cause the pinning effect in some areas to be unclear, and the bonding between the surface oxide layer and the bonding layer coating is poor; if the scratch interval is too large, the number of oxide "nails" is insufficient, and the overall pinning effect of the bonding layer coating is not obvious; if the scratch depth is too large, the wrinkle angle of the oxide layer is too large, and it is easy to crack.
[0055] In a specific embodiment, the composition of the strong pinning effect bonding layer of the present application includes, by mass percentage: Al 10-11%, Co 23-24%, Cr 19-20%, Fe 22-23%, Ni 23-24%, Y 0.5-1%, Hf 0-0.5%.
[0056] See also Figure 1 The preparation method of the strong pinning effect bonding layer of the present application includes: putting the prepared high entropy alloy powder into a powder collecting tank, and placing the sample flat on the workpiece table; adjusting the laser power to 1200W~1800W, the laser rate to 20mm / s~100mm / s, and starting cladding; after the cladding is completed, grinding and polishing the surface with sandpaper to remove surface dirt and adhering powder; processing two groups of micro scratches with an interval of 1-20μm and a depth of 0.5-2μm on the surface of the polished coating, and the two groups of scratches intersect vertically; placing the coating after processing the micro scratches flat in a high-temperature furnace, adjusting the temperature to 550℃~850℃, and keeping it warm for 2~3h for pre-oxidation; after the pre-oxidation is completed, oxidizing at 800℃~1000℃ for 80~150h to obtain the strong pinning effect bonding layer of the present application, as shown in the schematic diagram Figure 2 shown.
[0057] In the present application, a high-entropy alloy coating with a dense structure and active elements agglomerated in a certain size and uniformly distributed in the coating structure is prepared through laser cladding technology. The polished coating is machined to form micron scratches at a certain distance on its surface. After pre-oxidation treatment, the active elements (Y, Hf, etc.) on the coating surface grow nano-scale oxide "nails" inward at the scratches before the Al element, and are distributed in a lattice pattern on the coating surface. The Al element grows a dense and complete Al2O3 layer around the oxide "nails". The oxide "nails" pin the Al2O3 layer to the coating surface, providing a higher bonding force for the oxide layer, thereby greatly improving the anti-oxidation performance of the bonding layer coating and the anti-stripping performance of the oxide layer.
[0058] The present application also provides a strong pinning effect bonding layer, which is prepared by the above-mentioned method for preparing a strong pinning effect bonding layer.
[0059] The strong pinning effect bonding layer provided in the present application includes a bonding layer coating and oxide "nails" formed in the bonding layer coating and evenly spaced apart, and an Al2O3 layer formed on the surface of the bonding layer coating. The spacing of the oxide "nails" is 1-20 μm, and the depth of the oxide "nails" is 1-3 μm. The oxide "nails" have good compatibility with the Al2O3 layer, and when observed under an electron microscope at 1500 times, they are tightly bonded and have no gaps.
[0060] The present application also provides the application of the strong pinning effect bonding layer prepared by the preparation method of the strong pinning effect bonding layer in hot end components. The hot end components may be, for example, an engine or an engine turbine blade.
[0061] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0062] Example 1
[0063] The strong pinning effect bonding layer of Example 1 is a high entropy alloy powder, and its components include: Al10.6wt%, Co23.6wt%, Cr 19wt%, Fe 22.5wt%, Ni 23.5wt%, Y 0.77wt%, and Hf 0.084wt%.
[0064] The preparation method of the strong pinning effect bonding layer of Example 1 includes: putting the prepared high entropy alloy powder into a powder collecting tank, and placing the sample flat on the workpiece table; adjusting the laser power to 1800W and the laser rate to 60mm / s, and starting cladding; after the cladding is completed, grinding and polishing the surface with sandpaper to remove surface dirt and adhering powder; processing micro scratches with an interval of 6μm and a depth of 1μm on the surface of the polished coating; placing the coating with processed micro scratches flat in a high-temperature furnace, adjusting the temperature to 700℃, and keeping it warm for 2 to 3h for pre-oxidation; after the pre-oxidation is completed, oxidizing at 900℃ for 100h to obtain the strong pinning effect bonding layer of Example 1.
[0065] The SEM image of the strong pinning effect bonding layer of Example 1 is as follows: Figure 3 As shown, the oxide layer and the bonding layer are continuous, dense and complete, the oxide "nail" interval is about 6μm, and the depth is 1-3μm. According to the standard "HB 5258-2000 Test Method for Determination of Oxidation Resistance of Steel and High-temperature Alloys", the oxidation weight gain rate of the coating at 900℃ is 0.06g / (mm 2 h), reaching the complete antioxidant level.
[0066] Example 2
[0067] The preparation method of the strong pinning effect bonding layer of Example 2 includes: placing the prepared high entropy alloy powder (same as Example 1) into a powder collecting tank, placing the sample flat on the workpiece table; adjusting the laser power to 1600W, the laser rate to 50mm / s, and starting cladding; after cladding, grinding and polishing the surface with sandpaper to remove surface dirt and adhered powder; processing micro scratches with an interval of 8μm and a depth of 1.5μm on the surface of the polished coating. The coating with micro scratches is placed flat in a high-temperature furnace, the temperature is adjusted to 800℃, and the temperature is kept for 2 to 3h for pre-oxidation; after the pre-oxidation is completed, oxidation is carried out at 900℃ for 100h to obtain the strong pinning effect bonding layer of Example 2.
[0068] The SEM image of the strong pinning effect bonding layer of Example 2 is as follows: Figure 4 As shown, the oxide layer is continuous, dense and complete, with oxide "nail" spacing of 8μm and a depth of 2-4μm. The coating oxidation weight gain rate at 900℃ is 0.05g / (mm 2 h), reaching the complete antioxidant level.
[0069] Example 3
[0070] The preparation method of the strong pinning effect bonding layer of Example 3 includes: placing the prepared high entropy alloy powder (same as Example 1) into a powder collecting tank, placing the sample flat on the workpiece table; adjusting the laser power to 1400W, the laser rate to 40mm / s, and starting cladding; after cladding, grinding and polishing the surface with sandpaper to remove surface dirt and adhered powder; processing micro scratches with a spacing of 4μm and a depth of 0.5μm on the surface of the polished coating. The coating with micro scratches is placed flat in a high-temperature furnace, the temperature is adjusted to 600℃, and the temperature is kept for 2 to 3h for pre-oxidation; after pre-oxidation, oxidize at 900℃ for 100h to obtain the strong pinning effect bonding layer of Example 3.
[0071] The SEM image of the strong pinning effect bonding layer of Example 3 is as follows: Figure 5 As shown, the oxide layer is continuous, dense and complete, with oxide "nail" spacing of 4μm and a depth of 1-2μm. The coating oxidation weight gain rate at 900℃ is 0.05g / (mm 2 h), reaching the complete antioxidant level.
[0072] Example 4
[0073] The preparation method of the strong pinning effect bonding layer of Example 4 includes: placing the prepared high entropy alloy powder (same as Example 1) into a powder collecting tank, placing the sample flat on the workpiece table; adjusting the laser power to 1400W, the laser rate to 40mm / s, and starting cladding; after cladding, grinding and polishing the surface with sandpaper to remove surface dirt and adhered powder; processing micro scratches with an interval of 15μm and a depth of 0.5μm on the surface of the polished coating. The coating with micro scratches is placed flat in a high-temperature furnace, the temperature is adjusted to 600℃, and the temperature is kept for 2 to 3h for pre-oxidation; after pre-oxidation, oxidize at 900℃ for 100h to obtain the strong pinning effect bonding layer of Example 4.
[0074] The SEM image of the strong pinning effect bonding layer of Example 4 is as follows: Figure 6 As shown, the oxide layer is continuous, dense and complete, with oxide "nail" spacing of 15μm and a depth of 1-2μm. The coating oxidation weight gain rate at 900℃ is 0.06g / (mm 2 h), reaching the complete antioxidant level.
[0075] Comparative Example 1
[0076] The preparation method of the bonding layer of Comparative Example 1 includes: placing the prepared high entropy alloy powder (the same as Example 1) into a powder collecting tank, and placing the sample flat on a workpiece table; adjusting the laser power to 1600 W and the laser rate to 50 mm / s, and starting cladding; after the cladding is completed, grinding and polishing the surface with sandpaper to remove surface dirt and adhered powder; placing the ground and polished coating flat in a high-temperature furnace, adjusting the temperature to 600°C, keeping it warm for 2 to 3 hours, and pre-oxidizing; after the pre-oxidation is completed, oxidizing at 900°C for 100 hours to obtain the bonding layer of Comparative Example 1.
[0077] The SEM of the bonding layer of Comparative Example 1 is as follows Figure 7 and Figure 8 As shown in the figure, the oxide layer cracks. The oxidation weight gain rate of the coating at 900℃ is 0.14g / (mm 2 h), is antioxidant grade.
[0078] Comparative Example 2
[0079] The preparation method of the strong pinning effect bonding layer of comparative example 2 includes: placing the prepared high entropy alloy powder (same as in Example 1) into a powder collecting tank, placing the sample flat on a workpiece table; adjusting the laser power to 1400W and the laser rate to 40mm / s, and starting cladding; after cladding, grinding and polishing the surface with sandpaper to remove surface dirt and adhered powder; processing micro scratches with an interval of 8μm and a depth of 0.5μm on the surface of the polished coating. The coating with processed micro scratches is placed flat in a high-temperature furnace, and is directly oxidized at 900℃ for 100h without pre-oxidation to obtain the strong pinning effect bonding layer of comparative example 2.
[0080] The SEM image of the strong pinning effect bonding layer of Comparative Example 2 is as follows: Fig. 9 As shown in the figure, the oxide layer is severely cracked. The oxidation weight gain rate of the coating at 900℃ is 0.17g / (mm 2 h), is antioxidant grade.
[0081] Comparative Example 3
[0082] The preparation method of the strong pinning effect bonding layer of comparative example 3 includes: placing the prepared high entropy alloy powder (same as in Example 1) into a powder collecting tank, placing the sample flat on the workpiece table; adjusting the laser power to 1400W, the laser rate to 40mm / s, and starting cladding; after cladding, grinding and polishing the surface with sandpaper to remove surface dirt and adhered powder; processing micro scratches with an interval of 25μm and a depth of 0.5μm on the surface of the polished coating. The coating with micro scratches is placed flat in a high-temperature furnace, the temperature is adjusted to 600℃, and the temperature is kept for 2 to 3h for pre-oxidation; after the pre-oxidation is completed, oxidation is carried out at 900℃ for 100h to obtain the strong pinning effect bonding layer of comparative example 3.
[0083] The SEM image of the strong pinning effect bonding layer of Comparative Example 3 is as follows: Fig.10 As shown, the oxide layer cracks. The coating oxidation weight gain rate at 900℃ is 0.15g / (mm 2 h), is antioxidant grade.
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0085] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A method for preparing a strong pinning effect bonding layer, characterized in that: include: preparing a bonding layer coating on a substrate surface; Processing the surface of the bonding layer coating to obtain scratches distributed at intervals; The adhesive layer coating with the scratches is pre-oxidized and oxidized in sequence to obtain the adhesive layer with strong pinning effect.
2. The method for preparing a strong pinning effect bonding layer according to claim 1, characterized in that: The step of preparing a bonding layer coating on the surface of a substrate comprises: preparing the bonding layer coating on the surface of the substrate by laser cladding technology.
3. The method for preparing a strong pinning effect bonding layer according to claim 2, characterized in that: The laser power of the laser cladding is 1200W-1800W, and the laser speed is 20mm / s-100mm / s.
4. The method for preparing a strong pinning effect bonding layer according to claim 1, characterized in that: After the bonding layer coating is prepared on the surface of the substrate, the method further includes: grinding and polishing the bonding layer coating.
5. The method for preparing a strong pinning effect bonding layer according to claim 1, characterized in that: The components of the bonding layer coating include, by mass percentage, 10-11% Al, 23-24% Co, 19-20% Cr, 22-23% Fe, 23-24% Ni, 0.5-1% Y, and 0-0.5% Hf.
6. The method for preparing a strong pinning effect bonding layer according to claim 1, characterized in that: The pre-oxidation temperature is 550° C. to 850° C., and the heat preservation time is 2 to 3 hours.
7. The method for preparing a strong pinning effect bonding layer according to claim 1, characterized in that: The oxidation temperature is 800° C. to 1000° C., and the oxidation time is 80 to 150 hours.
8. The method for preparing a strong pinning effect bonding layer according to any one of claims 1 to 7, characterized in that: The interval between the scratches is 1-20 μm, and the depth of the scratches is 0.5-2 μm.
9. A strong pinning effect bonding layer, characterized in that: The method for preparing a strong pinning effect bonding layer as described in any one of claims 1 to 8 is used to prepare the bonding layer.
10. Application of a strong pinning effect adhesive layer prepared by the method for preparing a strong pinning effect adhesive layer according to any one of claims 1 to 8 in a hot end component.